(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
استهدفت الدراسة التعرف على بعض الخصائص الشخصية للمزارعين من رجال ونساء، وشبكة علاقاتهم في المجتمع المحلي، ومشكلات التعامل مع الأطراف المعنية ومقترحاتهم لحلها، ودور وسائل الإعلام الجماهيري كمصدر للمعلومات الزراعية، ودور العمل التشاركي في المجتمع المحلي ومعوقاته. ولتحقيق أهداف الدراسة تم تصميم استمارة استبيان وجمع البيانات من خلال عينة عشوائية من المزارعين في قريتين تتبعان محافظتي اللاذقية وطرطوس، وبلغ حجمها/ 100/ مزارعاً موزعة مناصفة على كل من القريتين والمزارعين من الرجال والنساء. وامتدت عملية جمع البيانات خلال الفترة الواقعة من15 أيار إلى24 حزيران لعام 2006، وتم استخدام الجداول التكرارية والنسب المئوية في التحليل الإحصائي للبيانات. وقد أوضحت النتائج أن (46%) من الرجال و( 56%) من النساء يتعامل بشكل دائم مع جماعات الأقارب والأصدقاء. كما أن (74%) من الرجال يتعامل بشكل دائم مع التجار والصيدليات و(68%) من النساء لا يتعاملن معهم. ووجد أن (80%) من الرجال يتعامل بشكل متقطع، و(52%) من النساء لا يتعاملن مع الوحدة الإرشادية، و(50%) من الرجال يتعامل بشكل متقطع و(90%) من النساء لا تتعامل مع المصرف الزراعي. ولوحظ أن (80%) من الرجال و(70%) من النساء يتابعون الراديو والتلفزيون، وقد أشار جميعهم إلى أهميتها. بينما وجد أن (60%) من الرجال، و(84%) من النساء لا يقرؤون المجلات والنشرات. وقد أشار (66%) من الرجال و( 74%) النساء إلى عدم أهميتها. The study aimed to identify some personal characteristics of farmers, both males and females, as well as their local and social networks. The study also identified their problems and their way of solving them. The role of the mass media as a source of agricultural information as well as the role of community participation and their obstacles were also investigated. The study was requested to design questionnaire for farmers. The total number of completed questionnaires(100) farmers, distributed fifty- fifty between farmers (male and female) in two villages in Latakia and Tartous. The process of data collection started in 15 May, and it was completed in 24 June 2006. The most important results of show that about (46%) of males and (56%) of females are in continuous contact with kinship and neighbors always. There are (74%) of males deal with traders always, while (68%) of females do not treat with them. (80%) of males deal with extension unit and (50%) deal with credit decimally, while (52%) of female do not treat with extension unit, and (90%) do not treat with credit. Most farmers (80%) of males and (70%) females watch Radio and TV, and they consider it very important; while most of farmers (60%) males and (84%) females do not read journals and publications, and they see it not important.